2021
DOI: 10.20944/preprints202108.0356.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Land-use/Land-cover Changes and Deforestation in Effan Forest Reserve, Kwara State, Nigeria

Abstract: Remote sensing/GIS techniques are a versatile tool for x-raying serial forest structural changes in retrospect. It would be impossible to evaluate past occurrences and changes in forest extents in past decades at Effan Forest Reserve without non-conventional means. Therefore, we adopted remote sensing technology using Landsat images to evaluate land-use change and degradation rates in the area with a view to ascertaining causal factors for possible minimization of forest degradation in Effan Forest Reserve. La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“…This result is consistent with those of Hamunyela, et al [4] and Kilungu, et al [5], who reported a decrease in primary (montane) forest in the Kilimanjaro WHS, Tanzania. Also, the result is similar to those of Adeyemi & Owolabi [51]; Sievers, et al [13]; Zeb [52], and Htun, et al [48] who showed decreasing primary/mangrove/dense/closed forests in Effan Forest Reserve in Nigeria, Sundarbans natural WHS in India, the District Chitral in Pakistan, and Popa Mountain Park in Central Myanmar, respectively. Also, the result is similar to those of Morin, et al [29] and Ullah, et al [53] who reported reductions in forest land cover in the Dilijan National Park of Armenia and Teknaf Wildlife Sanctuary of Bangladesh, respectively.…”
Section: Resultssupporting
confidence: 87%
“…This result is consistent with those of Hamunyela, et al [4] and Kilungu, et al [5], who reported a decrease in primary (montane) forest in the Kilimanjaro WHS, Tanzania. Also, the result is similar to those of Adeyemi & Owolabi [51]; Sievers, et al [13]; Zeb [52], and Htun, et al [48] who showed decreasing primary/mangrove/dense/closed forests in Effan Forest Reserve in Nigeria, Sundarbans natural WHS in India, the District Chitral in Pakistan, and Popa Mountain Park in Central Myanmar, respectively. Also, the result is similar to those of Morin, et al [29] and Ullah, et al [53] who reported reductions in forest land cover in the Dilijan National Park of Armenia and Teknaf Wildlife Sanctuary of Bangladesh, respectively.…”
Section: Resultssupporting
confidence: 87%